Economic integration worldwide, regional, sectoral : proceedings of the fourth congress of the International Economic Association held at Budapest, Hungary - Machlup, Fritz; International Economic Association (London ; New York ; New York : Macmillan Press ; distributed in the U.S. by Halsted Press, 1976)
This is the proceedings of the fourth congress of the International Economic Association held at Budapest, Hungary on economic integration.
Includes bibliographical references and index.
28/2/19
Loans
Keywords: International economic integration